Expression and characterization of Ov-47, a dominant antigen of Onchocerca volvulus - Ghoyomu, S.M.; Souopgui, J.; Pelle, Roger; Titanji, V.P.K. (Elsevier, 2002)
The expression and characterization of a recombinant antigen termed Ov-47 are described. Ov-47 was identified and isolated from a lambda gt-11 eDNA expression library derived from adult female Onclrucercu volvukrs mRNA using rabbit antiserum raised against the surface proteins of O. vulvulcw female worms. The antiserum was earlier found to mediate, in vitro, cytoadherence and cytotoxicity reactions to microfilariae in the presence of heat-labile serum factors. The deduced amino acid sequence of the gene was assigned the ENIBL GenBank Accession No. Y t5993. The open reading frame (1077 bp) of the gene was then subcloned into pQE60 and expressed in Escherchia coli JM 109 cells. The gene encodes a protein with an apparent molecular weight of 47,0 Da as revealed by SDS-PAGE. Up to (00 Itg/ml pure Ov-47 recombinant protein could be isolated from E. coli cultures by Ni-agarose affinity chromatography. The 47-kDa protein was recognized by sera from both infected and endemic normal subjects. The parent protein was found to have a molecular weight of 60 kDa. IeG3 subclass responses to Ov-47 were significantly higher in endemic normals than in infected subjects (P < 0.05). In contrast, IgGy responses were higher in infected subjects than in endemic normals (P < 0.05). I?GZ response exhibited marked age dependency with lower responses in younger patients, which rose to higher levels in elderly patients. IgGt, IgG3, and IgG4 responses did not show any age dependency. This study clearly shows that Ov-47 is a dominant antigen of O. volvetlus adult worms with an important role in the host-parasite-interplay.